1995
DOI: 10.1093/ajcn/61.3.549
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of red wine with meals reduces the susceptibility of human plasma and low-density lipoprotein to lipid peroxidation

Abstract: The effect of consumption of red or white wine (11% alcohol) with meals on the propensity of plasma and low-density lipoprotein (LDL) to undergo lipid peroxidation was studied in 17 healthy men who were divided into two groups: 8 received 400 mL red wine/d for 2 wk, and 9 received a similar amount of white wine. Red wine consumption for 2 wk resulted in a 20% reduction in the propensity of plasma to undergo lipid peroxidation (in the presence of a free-radical-generating system) as determined by the thiobarbit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
300
4
4

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 598 publications
(326 citation statements)
references
References 44 publications
12
300
4
4
Order By: Relevance
“…This is true in spite of a 15.7% vitamin E signi®cant enrichment and a more highly signi®cant increase in the vitamin Eabis-allylic carbon molar ratio of LDL, which is expected to be the mark of an improved protection against oxidation (since an antioxidant parameter at the numerator is associated to a pro-oxidant parameter at the denominator). This lack of improved protection is not in agreement with other results (Kondo et al, 1994;Fuhrman et al, 1995) where the action of red or white wine consumption was analyzed using similar LDL preparative procedure. The difference, however, may be explained by the supply of an integrate wine.…”
Section: Discussioncontrasting
confidence: 75%
“…This is true in spite of a 15.7% vitamin E signi®cant enrichment and a more highly signi®cant increase in the vitamin Eabis-allylic carbon molar ratio of LDL, which is expected to be the mark of an improved protection against oxidation (since an antioxidant parameter at the numerator is associated to a pro-oxidant parameter at the denominator). This lack of improved protection is not in agreement with other results (Kondo et al, 1994;Fuhrman et al, 1995) where the action of red or white wine consumption was analyzed using similar LDL preparative procedure. The difference, however, may be explained by the supply of an integrate wine.…”
Section: Discussioncontrasting
confidence: 75%
“…Nonetheless in spite of our failure to demonstrate a signi®cant change in in vitro plasma antioxidant capacity following rutin supplementation, the possibility that the increased plasma concentration of¯avonoids may afford a protective effect by metal chelation still remains. In vivo the oxidation of LDL has been shown to be a mediating factor in atherosclerosis development (Aviram, 1983;Palinski et al, 1989;Steinberg et al 1989) and Fuhrman et al (1995) have reported a 20% reduction in the propensity of plasma to undergo oxidation following 2 weeks of supplementation with 400 ml red wineaday. Recently McAnlis et al, (1999) have shown that, although dietarȳ avonoids are extensively absorbed, they do not accumulate within the LDL but are tightly bound to plasma proteins located predominantly within the HDL fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst there have been numerous reports of the protective effects of polyphenols in altering LDL susceptibility to oxidation in vitro (DeWhalley et al, 1990; Negre- Salvayre & Salvayre, 1992), there have been few reports of a similar in vivo activity. The consumption of red wine with meals reduces the propensity of human plasma and LDL to undergo lipid peroxidation (Fuhrman et al, 1995). The report of increased resistance of human LDL to ex vivo oxidation following 2 weeks supplementation with thē avonoid glycoside, glabridin, suggests that dietary supplementation with¯avonoids may offer protection against the onset of atherosclerosis (Fuhrman et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The selection of an appropriate sorbent is of major importance to achieve acceptable clean-up and extraction yield [60]. Five different MEPS sorbents namely the silica-based C2, C8 and C18 phases (suitable for lipophilic analytes), as well as the mixed bonded silica C8/SCX (suitable for polar analytes such as acidic and basic compounds) containing both reversed phase and cationic exchange groups, and the polar silica phase (SIL), were tested.…”
Section: Nature Of Sorbentmentioning
confidence: 99%